Strategies of Diskominfo SP to Obtain Support to Create Website Based Online System for Kelurahan - Danardono, Arso; Rahmanto, Andre; Hastjarjo, Sri (KnE Social Sciences, 2019)
In order to improve public service in village (kelurahan), the Local Government of Surakarta create innovation called website based online system (WBOS). The system is intended to facilitate interaction between village government and its citizens utilizing Information Communication Technology (ICT). It is created by the Department of Communications Information Statistics and Coding Service (Dinas Komunikasi Informatika Statistik dan Persandian/Diskominfo SP) and can be used to disseminate government information and publish the village’s potentials. In an effort to create the website, Diskominfo SP need to obtain support from kelurahan. This research is aimed at identifying encountered obstacles and strategies used to overcome it. The structuration theory of Anthony Giddens is employed to analyze the phenomenon and the Three Processes Model is used to elaborate the activities conducted by Diskominfo SP. The data is obtained by interviews and documentation study. The interviews are conducted with Diskominfo SP, web administrators, and local youth organization (Karang Taruna Kelurahan). The results show that the encountered obstacles are; limited number of personnels available in the village, limited number of personnels in the villages who master in computer science, the village’s personnels’ high work volume, and the limited opportunities to create innovation in villages. Meanwhile, the strategies used are making a simple web design, appointing web administrators from village official, local youth organization and SMEs community, conducting special training for web administrators, and inviting local communities to participate in enriching web content and web development. Keywords: Strategies, Online System, Website, Diskominfo SP, Surakarta